2019
DOI: 10.5958/0974-0279.2019.00006.5
|View full text |Cite
|
Sign up to set email alerts
|

Crop diversification in Odisha: an analysis based on panel data

Abstract: Crop diversification is considered as a pathway to promote agricultural development. The present paper examines the subtleties of crop diversification in Odisha, an eastern state in India through spatial trends across 30 districts and determinants of crop diversification. The analysis carried out from 1993-94 to 2012-13 indicates sluggishness and unevenness in crop diversification. The coastal districts lack diversification while several of the districts falling in the southern part of the state tend to be mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…Cropping intensity which is defined as the ratio of GCA to net sown area, is expected to have a positive impact on crop diversification because farmers have the tendency to rotate crops to improve farm sustainability (Kumar & Gupta, 2015a; Nayak & Kumar, 2019a). In align with the previous studies, we find a positive and significant value of the variable LNCI.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cropping intensity which is defined as the ratio of GCA to net sown area, is expected to have a positive impact on crop diversification because farmers have the tendency to rotate crops to improve farm sustainability (Kumar & Gupta, 2015a; Nayak & Kumar, 2019a). In align with the previous studies, we find a positive and significant value of the variable LNCI.…”
Section: Resultsmentioning
confidence: 99%
“…Growing different types of crops throughout the year requires regular irrigation facility, so households having access to regular irrigation water sources are expected to diversify crops. Several studies have found that irrigation influences crop diversification positively (Abro, 2012; Aheibam & Singh, 2017; Birthal et al, 2006; Dube & Guveya, 2016; Kumar et al, 2012; Kumar & Gupta, 2015a, 2015b; Rahman & Kazal, 2015), while others show that irrigation discourages diversification (Benin, Smale, Pender, Gebremedhin, & Ehui, 2004; Jha, Tripathi, & Mohanty, 2009; Joshi, Birthal, & Minot, 2006; Joshi, Joshi, & Birthal, 2006; Nayak & Kumar, 2019a; Rao, Joshi, Kumar, & Ganguly, 2008). In our study we did not find any significant relationship between irrigation and crop diversification.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The increased demand and price for the vegetables also lead to crop diversification [3]. There are different factors like rain-fall, fertilizer, irrigation, farmer's knowledge etc are responsible for crop diversification in the study area [4] but sometimes due the climate change and unproductive rain there is crop concentration rather than diversification [5].…”
Section: Introductionmentioning
confidence: 99%
“…They can produce diversified foods; therefore, they are almost self-reliant and less dependent on purchases. Farms may also be specializing in growing and selling commercial crops and, if necessary, buying most of its food needs (Nayak and Kumar 2019). The production decision is majorly determined by the distance between the farm and market (transaction cost).…”
mentioning
confidence: 99%